Rutin Isolated from Chrozophora tinctoria Enhances Bone Cell Proliferation and Ossification Markers. (13th February 2018) - Abdel-Naim, Ashraf B.; Alghamdi, Abdullah A.; Algandaby, Mardi M.; Al-Abbasi, Fahad A.; Al-Abd, Ahmed M.; Eid, Basma G.; Abdallah, Hossam M.; El-Halawany, Ali M.
Abstract : Osteoporosis is a chronic disease in which the skeleton loses a weighty proportion of its mineralized mass and mechanical pliability. Currently available antiosteoporotic agents suffer adverse effects that include elevated risk of thrombosis and cancer. Phytochemicals may constitute a safer and effective option. In the current work, six flavonoids were obtained from Chrozophora tinctoria and identified as amentoflavone (1), apigenin-7- O - β -d -glucopyranoside (2), apigenin-7- O -6 ′ ′ - E - p -coumaroyl- β -d -glucopyranoside (3), acacetin-7- O - β -d -[ α -l -rhamnosyl(1→6)]3 ′ ′ - E - p -coumaroyl glucopyranoside (4), apigenin-7- O -(6 ′ ′ - Z - p -coumaroyl)- β -d -glucopyranoside (5), and rutin (6). An extensive review of the literature as well as NMR and mass spectral techniques was employed in order to elucidate the compound structures. Proliferation was enhanced in MCF7, MG-63, and SAOS-2 cells after exposure to subcytotoxic levels of the tested flavonoids. Rutin was chosen for subsequent studies in SAOS-2 cells. Rutin was not found to cause any alteration in the index of proliferation of these cells, when examining the cell cycle distribution by DNA flowcytometric analysis. Rutin was, however, found to increase osteocyte and osteoblast-related gene expression and lower the expression of RUNX suppressor and osteoclast genes. When examining the influence of rutin on vitamin D levels and the activity of alkaline phosphatase enzyme, it was found to enhance both, while decreasing acid phosphatase which is a marker of osteoporosis. Thus, rutin enhances proliferation and ossification markers in bone cells.